Lineages of crisp‑leaf lettuce for summer cropping resistant to Meloidogyne javanica and to Lettuce mosaic virus - Silva, Renata Rodrigues; Gomes, Luiz Antônio Augusto; Monteiro, Aline Beraldo; Maluf, Wilson Roberto; Filho, José Luiz Sandes de Carvalho; Massaroto, João Aguilar (Pesquisa Agropecuaria Brasileira, 2008)
The aim of this work was to select F4 lettuce families, derived from the cross 'Veronica' x 'Salinas 88 ', for summer cropping, type of leaves, and for resistance to Meloidogyne javanica and to Lettuce mosaic virus (LMV). First, evaluations were made for leaf colour, leaf limb, border type, and heat tolerance in the fi eld, in a complete blocks desing, in 15 F4 families previously selected, parent cultivars and, as control, the cultivar Regina 71 (butterleaf and tolerant to heat). Five replicates and eight plants per plot were used. As second step, the families were evaluated in greenhouse, in 128-cell expanded polystyrene trays, for resistance to LMV and root-knot nematodes. Score means of each family were compared to the means of each parental cultivar by Dunnett test at 5% probability. Family AFX007B-140-21, homozygous for root-knot nematodes, for LMV and heat tolerant, was the most promising. The cross between crisp and butter leaf cultivars can originate promising lineages both with crisp and butter leaves.